2008
DOI: 10.1590/s1516-35982008000700021
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça, componentes não-carcaça e composição tecidual e química da 12ª costela de cordeiros Santa Inês terminados em pasto com três gramíneas no período seco

Abstract: RESUMO -Foram avaliadas as características de carcaça, os componentes não-carcaça e o rendimento da 12 a costela de cordeiros Santa Inês terminados em pastejo rotacionado com três forrageiras tropicais (A. gayanus Kunth, cv. Planaltina, P. maximum Jacq., cv. Aruana e P. maximum Jacq., cv. Tanzânia), no período seco do ano. Utilizou-se delineamento inteiramente casualizado, com 11 ovinos (3 meses de idade e 18,8 ± 2,88 kg PV) em cada tratamento. Os animais receberam suplementação com concentrado em níveis cresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
6
3
3
Order By: Relevance
“…In this study, the shoulder and rib's weight and yields were lower than reported by Menezes et al (2008) who obtained values from 1.162 to 1.472 kg; 0.453 to 0.627 kg and 9.40% to 10.8% of half carcass; 23.0% to 25.2% of half carcass for shoulder and rib, respectively. In Menezes et al (2008)'s study, the standards cuts of meats were different compared with the present trial, contributing for the differences observed in weight and shoulder and rib's yield.…”
Section: Resultscontrasting
confidence: 81%
See 3 more Smart Citations
“…In this study, the shoulder and rib's weight and yields were lower than reported by Menezes et al (2008) who obtained values from 1.162 to 1.472 kg; 0.453 to 0.627 kg and 9.40% to 10.8% of half carcass; 23.0% to 25.2% of half carcass for shoulder and rib, respectively. In Menezes et al (2008)'s study, the standards cuts of meats were different compared with the present trial, contributing for the differences observed in weight and shoulder and rib's yield.…”
Section: Resultscontrasting
confidence: 81%
“…Clementino et al (2007) In this study, the leg's yields were higher than reported by Menezes et al (2008) which showed values of 28.4% to 29.9%. Probably, the different animal genotype used promoted these differences in leg's weight.…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…Left half carcass was separated in shoulder, leg (section between the first and the second sacral vertebrae) and other parts (half carcass subtracted from the leg and shoulder). The area of the Longissimus dorsi muscle (loin eye area -LEA), measured using the grid points methodology, and thickness of subcutaneous fat (fat thickness -FT) were measured in the section made between the 12 th and 13 th ribs (MENEZES et al, 2008;COSTA et al, 2012).…”
Section: Methodsmentioning
confidence: 99%